1982
DOI: 10.1159/000153327
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Antigen, Serum Protein and Red Cell Enzyme Polymorphisms in Eastern Highlanders of New Guinea

Abstract: A series of 1,187 blood samples from eight population groups in the Eastern Highlands of Papua New Guinea were tested for genetic variation in blood groups, serum proteins and red cell enzyme systems. The populations belonged to the language groups Gahuku-Asarc-Bena Bena, Kamano, Yagaria, Keiagana, Fore, Agarabe, Auyana and Tairora. Polymorphic variation was found in the ABO, MNS, P1; Rh, Hp, Tf, SEP, 6-PGD, ADA, MDH, and PGM genetic systems. East to West variation was shown in the language groups; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…1 We and others have conducted a number of epidemiologic surveys within PNG to improve our understanding of the relationships between malaria parasite infection and disease, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] anti-malarial drug and vaccine effectiveness, [17][18][19] and human genetic polymorphisms. [20][21][22][23][24][25][26][27][28] These studies have shown that all four Plasmodium species (P. falciparum [PF], P. vivax [PV], P. malariae [PM], and P. ovale [PO]) cause infection in PNG. Although PF is presently the predominant malaria parasite species, PV and PM were observed to be the majority malaria parasite species before the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…1 We and others have conducted a number of epidemiologic surveys within PNG to improve our understanding of the relationships between malaria parasite infection and disease, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] anti-malarial drug and vaccine effectiveness, [17][18][19] and human genetic polymorphisms. [20][21][22][23][24][25][26][27][28] These studies have shown that all four Plasmodium species (P. falciparum [PF], P. vivax [PV], P. malariae [PM], and P. ovale [PO]) cause infection in PNG. Although PF is presently the predominant malaria parasite species, PV and PM were observed to be the majority malaria parasite species before the 1980s.…”
Section: Introductionmentioning
confidence: 99%